Efeito da suplementação de carotenoides do urucum sobre a resistência da LDL-colesterol à oxidação e o status oxidativo em indivíduos saudáveis - Conte, Lisiane (2018)
Cardiovascular diseases are a group of varied diseases, including obstructive diseases, such coronary artery disease and stroke, which are the leading causes of death in the world. These obstructive events are consequence of a process, known as atherosclerosis, characterized by the accumulation of fibrous and lipid material in the arterial wall of large and medium-sized vessels. Atherosclerosis development involves several processes, among them lipids accumulation, endothelial dysfunction, inflammation and, especially, oxidative stress, which is responsible of low-density lipoprotein (LDL) oxidation. Thus, researchers have found alternatives to prevent atherosclerosis development and progression, such the consumption of antioxidant-rich food. Epidemiological studies have shown that higher serum levels of some carotenoids, such lycopene, are related to a lower cardiovascular risk. Despite this, some studies have questioned lycopene supplementation benefits. Therefore, researches have highlighted other carotenoids in the last few years. Among them, the carotenoids present in annatto seeds (Bixa orellana), bixin and norbixin, whose antioxidant and antiatherogenic potential has already been demonstrated by in vitro and animal studies. However, there are no reports in literature about its short and long-term consumption effects in humans. Therefore, the objective of this study was to evaluate the effects of bixin, norbixin and lycopene consumption for 7 days on biochemical and oxidative stress biomarkers, as well as the susceptibility of LDL to copper-induced oxidation in healthy individuals. A randomized, double blind, placebo-controlled, cross-over study were made with 16 healthy volunteers (8 men and 8 women), who received each one of the four treatments (bixin, norbixin, lycopene or placebo), at dose of 0.05 mg / kg body weight orally. The biochemical and oxidative stress parameters analysed were not affected by any treatment. However, in comparison to placebo, bixin supplementation reduced the oxidation rate of the lipid moiety of LDL and serum levels of nitric oxide metabolites (NOx). Besides, the positive correlation found between NOx levels and the susceptibility of LDL to ex-vivo oxidation, suggesting that the reduction of NOx levels could be the mechanism responsible for the protective action of bixin. These results suggest that bixin has a biological action that may help in atherosclerosis prevention.